Human health screening level risk assessments of tertiary-butyl acetate (TBAC): Calculated acute and chronic reference concentration (RfC) and Hazard Quotient (HQ) values based on toxicity and exposure scenario evaluations. (February 2015) - Bus, James S.; Banton, Marcy I.; Faber, Willem D.; Kirman, Christopher R.; McGregor, Douglas B.; Pourreau, Daniel B.
Abstract: A screening level risk assessment has been performed for tertiary-butyl acetate (TBAC) examining its primary uses as a solvent in industrial and consumer products. Hazard quotients (HQ) were developed by merging TBAC animal toxicity and dose-response data with population-level, occupational and consumer exposure scenarios. TBAC has a low order of toxicity following subchronic inhalation exposure, and neurobehavioral changes (hyperactivity) in mice observed immediately after termination of exposure were used as conservative endpoints for derivation of acute and chronic reference concentration (RfC) values. TBAC is not genotoxic but has not been tested for carcinogenicity. However, TBAC is unlikely to be a human carcinogen in that its non-genotoxic metabolic surrogates tertiary-butanol (TBA) and methyl tertiary butyl ether (MTBE) produce only male rat α-2u-globulin-mediated kidney cancer and high-dose specific mouse thyroid tumors, both of which have little qualitative or quantitative relevance to humans. Benchmark dose (BMD)-modeling of the neurobehavioral responses yielded acute and chronic RfC values of 1.5 ppm and 0.3 ppm, respectively. After conservative modeling of general population and near-source occupational and consumer product exposure scenarios, almost all HQs were substantially less than 1. HQs exceeding 1 were limited to consumer use of automotive products and paints in a poorly ventilated garage-sized room (HQ = 313) and occupational exposures in small and large brake shops using no personal protective equipment or ventilation controls (HQs = 3.4–126.6). The screening level risk assessments confirm low human health concerns with most uses of TBAC and indicate that further data-informed refinements can address problematic health/exposure scenarios. The assessments also illustrate how tier-based risk assessments using read-across toxicity information to metabolic surrogates reduce the need for comprehensive animal testing.